Sustitución parcial de la harina de trigo con diferentes harinas de camote y su efecto en la calidad panadera. - Bernal Bailón, Ingrid Ibeth (2015)
The purpose of this research was to determine the baking quality in the development of a type of bread from the partial substitution of wheat flour by different sweet potato flour (five varieties), employing analysis rheological behaviors identifying premixes and aptitudes of each variety. For the finished product were measured characteristics such as hardness, elasticity, firmness, chewiness and bread volume; variables that determine the quality and pattern of consumption. Was applied to a sensory panel sheets using a hedonic scale acceptability to determine the best treatment. Among the results obtained regarding the rheology analyzes premixes flours, a1 level range corresponding to the lower reflected Toquecita amylase activity and low starch damage, good performance in the kneading step, proving optimal for the process flour baking; because it can withstand high mechanical stress in this process. As for the factors in studies morado Ecuador variety bread was better treatment volume also is at one with the texture analysis Brookfield: cycles hardness, chewiness and firmness, factors determining the freshness of bread thus preference consumption. While due to attributes: smell, color and flavor, tasting panel Guayaco morado variety that was the highlight. Concluding that in each of the stages of preparation of bread premixes tend to have different behaviors depending on the variety of potato containing the premix.